Chlamydia trachomatis Infection Control Programs: Lessons Learned and Implications for Vaccine Development - Jean M. Chavez; Rodolfo D. Vicetti Miguel; Thomas L. Cherpes (Hindawi Limited, 2011)
Chlamydia trachomatis control efforts that enhance detection and treatment of infected women may paradoxically increase susceptibility of the population to infection. Conversely, these surveillance programs lower incidences of adverse sequelae elicited by genital tract infection (e.g., pelvic inflammatory disease and ectopic pregnancy), suggesting enhanced identification and eradication of C. trachomatis simultaneously reduces pathogen-induced upper genital tract damage and abrogates formation of protective immune responses. In this paper, we detail findings from C. trachomatis infection control programs that increase our understanding of chlamydial immunoepidemiology and discuss their implications for prophylactic vaccine design.